The Ethics of Preaching in the Digital Space: A Study of the Phenomenon of Ustaz Influencers on Social Media - Robby Aditya Putra; Upi Zahra; Aisyah Rochmah Nuraini (Wardah, 2026)
The rapid growth of digital technology has significantly transformed the practice of Islamic preaching, particularly through the emergence of preacher influencers on social media platforms. This study is conducted due to the increasing influence of digital preaching on public religious understanding and the growing concern over ethical challenges arising from the integration of religious messages with media logic. The study is based on the hypothesis that digital preaching practices are influenced by algorithmic systems and audience engagement demands, which may create tension between communicative effectiveness and the ethical principles of Islamic preaching. This research employs a qualitative approach with a phenomenological design. Data were collected through non-participant observation of preaching activities on social media and document analysis of digital content, including videos, captions, comments, and promotional materials. The data were analyzed using thematic analysis to identify patterns, trends, and ethical implications of digital preaching practices. The results show that digital preaching is predominantly presented in short, visually engaging, and emotionally driven formats that align with audience preferences and platform algorithms. However, this adaptation leads to the simplification of religious messages, the potential for misinterpretation, and the emergence of sensational communication styles. In addition, monetization practices indicate that preaching activities are increasingly integrated into the digital economic ecosystem. These findings confirm that there is a tension between the ethical values of preaching and the demands of digital media environments. This study concludes that there is a need to develop a contextual and adaptive ethical framework for digital preaching that maintains the integrity of Islamic values while responding to the dynamics of social media. The findings contribute to the advancement of preaching and communication studies by emphasizing the importance of ethics in digital religious practices.